U.S Travel Ban Policy on 6 Muslim Countries as Attempt of Donald Trump Government in Counter-Terrorism in 2017: 1. Introduction, 2. Methodology, 3. Finding and Discussion, 4. Conclusion - Ida Susilowati (UNIDA Gontor, 2024)
This research is a U.S. foreign policy review of Travel Ban policy during Donald J. Trump's 2017 administration. The travel ban policy, United States imposes policies on Muslim-majority countries as an attempt to reduce the entry of immigrants into the U.S. This research aims to discuss the aspects that led to the United States Travel Ban policy against immigrants from Muslim countries where immigrants entering the United States are considering be able to influence the stability of American security. This research will use the concept of national security, which will explain the security priorities of the U.S. state, one of which is to protect the country from terror attacks. The idea of foreign policy is used to analyze how the policy can be implemented by the U.S. This research, uses the qualitative method with data collection technique through library research. The results of this research showed that in travel ban policy-making, there are several revisions until approved by the Supreme Court taking into account various aspects by stakeholders and its works on reducing the immigrant entry into the U.S. especially from Muslim countries